Water pipeline condition assessment - Ruchti, George F. (The American Society of Civil Engineers, 2017)
MOP 134 provides water utilities with an appropriate path for adequately determining the structural status of an individual transmission pipeline or pipeline system.
Keywords: Water-pipes -- Testing.; Water-pipes -- Evaluation.; elektronické knihy; electronic books